Analysis of the Implementation of the Murabahah Agreement at Bank Syariah Indonesia (BSI) Based on DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 - Hadist Sulistiawati; Deby Octafiani Putri; Syadzwina Rasyiah Iwani; Muthia Sartika Harahap; Hafidz Muhammad Hidayah (Jurnal Cendikia ISNU SU, 2025)
The development of the Islamic banking industry in Indonesia encourages financial institutions to ensure the conformity of their products with sharia principles, including in the implementation of murabahah contracts. This contract is one of the main financing instruments at Bank Syariah Indonesia (BSI) and must be implemented in accordance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000. This study aims to identify obstacles in the implementation of murabahah contracts in Bank Syariah Indonesia based on Fatwa DSN-MUI No.04/DSN-MUI/IV/2000, analyze its legal implications on customer rights and obligations, and analyze the conformity of its implementation with the fatwa. The research method used is normative juridical with a document study approach, examining financing agreements and contract implementation practices in the field. The results of the study show that the main obstacles in the implementation of murabahah contracts at BSI include the lack of customer understanding of the substance of the contract, lack of optimal socialization from the bank, and incompatibility between the bank's operational mechanism and the murabahah principle. The legal implications have an impact on the emergence of an imbalance of rights and obligations between customers and banks, especially when there is a default. In addition, the implementation of murabahah contracts at BSI, especially in pension financing products, has been quite consistent with the provisions of DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000, although there are still aspects that need to be improved to be fully in line with the established sharia principles. The conclusion of this study shows that although the implementation of the murabahah contract at BSI has been carried out in accordance with sharia in many aspects, improvements in literacy, internal procedures, and supervision are still needed so that compliance with the principle of muamalah can be maintained optimally.